Escherichia coli yqiG: pseudogene or functional allele for biohydrogen production? - Zakaria, Muhammad Azman; Mohd Yusoff, Mohd Zulkhairi; Hassan, Mohd Ali; Zakaria @ Mamat, Mohd Rafein; Maeda, Toshinari (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Pseudogene considered as non functional gene in many organisms. Based on the study, there are several pseodugenes embaded in Escherichia coli (E.coli) genome. yqiG is one of the pseudogenes found in E.coli.. Hydorgen is by-product produces during the degradation of glucose through glyclysis pathway. Theoritically, one mole of glucose may produces two mole of format and finally produce two mol of hydrogen. In this study, deletion of yqiG in E.coli has shown hydrogen deficiency during fermentation of glucose as carbon source. However, an opposite effect has observed from medium consist of formate as its substrate. Longer lag phase observed in formate medium during hydrogen production as the absence of YqiG. The result has confirmed that YqiG has a role during hydrogen production. It is probably, controls the gene expression and may helps on the maturation process of protein. Hence, YqiG is not a junk gene instead it is one of the essential proteins during hydrogen metabolism of E.coli.